Grammatical Errors Made by English Department Students in Writing Analytical Exposition Essay - Annisha Dyuli Adha (Majalah Ilmiah UPI YPTK, 2018)
This research was aimed to find out the students’ grammatical errors in writing analytical exposition essay. Besides, it is also to find out the processes of how the errors occur on the students’ writing and the causes of the errors. Sources of data were English department students of UNP in the fourth semester that were from four different classes, namely K1, K2, K3, and K4 in which each of the classes consisted of 30 students. So, total of the students was 120 students. However, only 30 students that were chosen randomly as samples of this research. The type of this research was a descriptive research. The data were collected by using writing test and interview. The findings of this research showed that the students’ grammatical errors in using simple present tense were in the use of subject, verb/ predicate, object, complement, and prepositional phrase. Besides, there were also the causes of the students’ errors, namely overgeneralization, ignorance of rule restriction, incomplete application of the rules, dan false concept hypothesized. From the data gotten, it could be concluded that the students made errors in six elements of grammar in analytical exposition essay.